Common Ayurvedic, Chinese traditional and Unani antidiabetic formulations- a review - Murudkar, Prajakta H.; Tambe, Mukul S.; Chandrasekar, S.B.; Boddeda, Bhavani; Pawar, Anil T. (Frontiers in Pharmacology, 2022)
Diabetes mellitus is the most widely recognized endocrine disorder which is influencing a bigger populace on the planet. There are various causes of diabetes, such as physical inactivity, obesity, family history, race, age, etc. Diabetes mellitus is associated with some life-threatening complications such as neuropathy, nephropathy, various eye diseases or retinopathy, cardiovascular disorders etc. For the treatment of diabetes and its complications, many synthetic hypoglycemic agents are available in the market. But, due to some serious side effects of synthetic formulations, people are opting for herbal remedies and, therefore, herbal remedies are now acquiring higher significance. Herbal remedies have lesser side effects and higher affordability and therefore can be preferably used over synthetic formulations for a long-term disorder like diabetes mellitus. Scientific research and reviews on the topic were collected from Science Direct, Scopus, PubMed, Google Scholar, and other relevant sources. The references of all the articles were screened manually for any additional information on popular polyherbal formulations in traditional Ayurvedic, Chinese and Unani medicine. In our study, we have studied commonly used traditional Ayurvedic, Chinese, and Unani antidiabetic formulations. These formulations have proved to be hypoglycemic in nature based on the research conducted by various scientists. Some of these formulations have also been studied for their detailed mode of action. From the results of various preclinical studies and clinical trials, it is found that these formulations have potent antidiabetic activity. This review highlights various Ayurvedic, Chinese and Unani polyherbal formulations utilized in the management of diabetes mellitus along with their preclinical and clinical exploration which will enhance the existing knowledge of the researchers.